Appendiceal mucocele presenting as acute appendicitis: a Case Report - Khan, Yasar; Daud, Muhammad; Ullah, Waseem; Faseeh, Muhammad; Attaullah, Aahan; Ur Rehman, Sahibzada Saad; Aslam, Farhan (International Journal of Pathology, 2025)
Background: Appendiceal mucocele represents cystic expansion of the appendix caused by mucin accumulation, frequently mimicking acute appendicitis clinically. Case Report: We present a case of elderly male who developed periumbilical discomfort, loss of appetite, and demonstrated positive rebound tenderness on examination. Imaging studies revealed an enlarged, perforated appendix which was initially interpreted as acute appendicitis. Intraoperatively, a significantly distended appendix measuring 4.0 x 2.5 cm containing thick, gelatinous mucoid contents was identified. Histological analysis established the diagnosis of appendiceal mucocele with mucin deposition and clear surgical margins. Postoperative recovery was uneventful. Complete surgical excision remains the primary treatment modality, with minimally invasive techniques being suitable for selected patients, although conventional open surgery was chosen in this instance due to perforation risk. Conclusion: This case emphasizes the importance of preoperative radiological assessment, good surgical technique to prevent rupture with subsequent pseudomyxoma peritonei, and definitive histopathological diagnosis.